Advanced Bio-Sensing System for Thermal Ambience Comfort - Mathe, R.P. (Institute of Electrical and Electronics Engineers Inc., 2019)
Traditional air conditioners are designed to maintain the indoor temperature and humidity at a desired level. They were not designed to monitor room occupants comfort and because of controlling the indoor air temperature they consume extra energy. The purpose of this project was to improve building occupants' thermal comfort and optimize the energy consumption by air conditioners. This was achieved by relating building occupant blood pressure to the temperature fed by air-conditioner. From the results of this study, it was noticed an inverse relationship between the blood pressure and Temperature. The project is relevant for improving the comfort of the people subjected to air-conditioned environment and helps to optimize the energy consumption by the air conditioners. Â© 2019 IEEE.